HISTORICAL BACKGROUND OFTHE ORIGIN AND EVOLUTION OF SARAIKI LANGUAGE INCENTRAL PAKISTAN;A CASE STUDY OF SARAIKI LANGUAGE IN DERA GHAZI KHAN - Ismut Ullah; Muhammad Gulfraz Abbasi; Muhammad Masood Abbasi; Yasir Arafat; Ghulam Asghar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Saraiki is considered one of the largest languages of South Punjab and it is also an ancient dialect of this region. The history of this dialect dates back to almost 4500 years in the Indus civilization. The people inhabiting South Punjab are also called as Saraiki. Dera Ghazi Khan is considered one of the important regions of Saraiki speaking people. Saraikidialect isalmost used by 86% people of Dera Ghazi Khan.Saraiki,as a major language was promoted by the intellectuals especially the Sufi poets in the region of South Punjab. This paper is an attempt to explore and highlight the origin and evolution of the Saraikilanguage and literature in Dera Ghazi Khan.